Social networks and bibliometrics on the use of UAVs in hydrological risk mapping in urban areas (Research, Society and Development, 2021)
This study aims to carry out research in the Scopus and Web of Science databases in order to search for works related to water mapping with a focus on risk areas using UAVs. The VOSViewer software generates infographics based on the node system displaying the main search terms, authors, recurring elements and keywords. Quantitatively categorizing the works into collaborating authors, approach to the topic, types of publications, main journals, indexes, main countries, collaboration networks and keywords, he indicated the main works pertinent to the topic, in which these were discussed to verify how the topic is approached. 91.15% of the works are written in English, with the US being the second country that publishes the most about, in the rear of China. The main terms concatenated in the research are UAV - Unmanned Aerial Vehicles, Photogrammetry and DEM - Digital Elevation Model, which allude to the use of UAVs to obtain the MDE and MDS by the photogrammetric method. Among the works, 10 presented methodological material and promising results in the use of UAV ́ for hydrological risk mapping, with emphasis on the work of Mazzoleni, Muthusamy Annis, Luppichini, who present image processing software (Agisoft PhotoScan) and hydrodynamic simulations of water pluvial and fluvial (FLO-2D and HEC-RAS). Therefore, this study made it possible to recognize methodological approaches, trends, difficulties and the advantages of the UAV tool in technical application, such as high precision, relatively low cost and reach in areas of difficult access.